1993
DOI: 10.3354/meps100003
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic methane production and oxidation within the algal maximum of the pycnocline: seasonal fine-scale observations in an anoxic estuarine basin

Abstract: High resolution profiles of methane concentration and potential methane-oxidation rates were used to test the importance of in situ production and oxidation in controlling methane structure and dynamics in the southern anoxic basin of the Pettaquamscutt Estuary, Rhode Island, USA. Profiles conducted in both April and August showed low but increasing methane concentrations in the surface oxic layer, a minor maximum about 0.75 m above the Eh = 0 boundary, a methane minimum just above Eh = 0, and a rapid increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 38 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…For example, it has been shown that fish feed preferentially on intense zooplankton thin layers, affecting the depth distribution and behavior of fish in Monterey Bay (Benoit-Bird, in review). While interactions within thin layers are just beginning to be investi gated, thin layers are likely to be important for a variety of biological processes, including growth rates, reproductive success, grazing, predator-prey encounters, nutrient uptake and cycling rates, as well as toxin production (Lasker, 1975;Mullin and Brooks, 1976;Sieburth and Donaghay, 1993;Donaghay and Osborn, 1997;Cowles et al, 1998;Hanson and Donaghay, 1998;Dekshenieks et al, 2001;Rines et al, 2002;McManus et al, 2008). In addition, the layering of the ocean and its plankton species into persistent thin structures acts to diversify and expand available ecological niche space.…”
Section: Ecological Importancementioning
confidence: 99%
“…For example, it has been shown that fish feed preferentially on intense zooplankton thin layers, affecting the depth distribution and behavior of fish in Monterey Bay (Benoit-Bird, in review). While interactions within thin layers are just beginning to be investi gated, thin layers are likely to be important for a variety of biological processes, including growth rates, reproductive success, grazing, predator-prey encounters, nutrient uptake and cycling rates, as well as toxin production (Lasker, 1975;Mullin and Brooks, 1976;Sieburth and Donaghay, 1993;Donaghay and Osborn, 1997;Cowles et al, 1998;Hanson and Donaghay, 1998;Dekshenieks et al, 2001;Rines et al, 2002;McManus et al, 2008). In addition, the layering of the ocean and its plankton species into persistent thin structures acts to diversify and expand available ecological niche space.…”
Section: Ecological Importancementioning
confidence: 99%
“…3a and 4) is consistently observed to coincide with increased particle accumulation at pycnoclines (Sieburth and Donaghay 1993). Thus, it is believed that these particles may act as anoxic microenvironments, as they are chemical hotspots providing both organic and inorganic substrates to sustain the anaerobic metabolism of pelagic microbiota (Ploug et al 1997).…”
Section: Autochthonous Methane Origin In the Reloncaví Fjordmentioning
confidence: 97%
“…Indeed, both autochthonous (plankton) and/or allochthonous (seston) particles can be colonized by decomposers (heterotrophs), which include a proportion of methanogens. Sieburth and Donaghay (1993) reported the existence of methanogenic bacterial consortia that can use methylated amines to create reduced micro-niches in oxygenated seawater and produce both CH 4 and HS − in the u p p e r o c e a n . M e th a n o g e n ic s u b s t r a t e s s u c h a s monomethylamine and trimethylamine, which are constituents of diatoms, dinoflagellates, and flagellate phytoplankton species, could be involved in CH 4 production during grazing by copepods (De Angelis and Lee 1994).…”
Section: Autochthonous Methane Origin In the Reloncaví Fjordmentioning
confidence: 99%
“…Sieburth and Donaghay, 1993;Zindler et al, 2013), permafrost soil, and wild animals), the difference should have anthropogenic sources such as livestock, rice cultivation, coaling mining, oil and gas, landfills, biomass burning, waste water, and others. However, natural sources have also been influenced by anthropogenic activities like the reduction of the area of natural wetlands or the impact on the permafrost soil.…”
Section: Discussionmentioning
confidence: 99%
“…Prather et al (2012) estimated for τ CH 4 -OH = 11.2 ± 1.3 years, for τ CH 4 -bacteria = 120 years, for τ CH 4 -strat = 150 years, and for a possible oxidation by atomic chlorine in the marine atmospheric boundary layer 200 years (according to Allan et al, 2007). For the period 1979-1993Dentener et al (2003 calculated for τ CH 4 -OH = 9.0±1.3 years. For the period 1978-2004Prinn et al (2005 estimated a lifetime of 10.2 (+0.9, −0.7) years.…”
Section: Introductionmentioning
confidence: 99%